A Case Report on Neurofibromatosis Associated with Infective Mass Tumor - Somanaboina Padmakar (Indian Journal of Pharmacy & Drug Studies, 2023)
A rare genetic disorder with many non-cancerous (benign) tumors of the skin (neurofibromas) and nerves is known as Neurofibromatosis. This disorder includes type 1-neurofibromatosis 1 (NF1), type 2-neurofibromatosis 2 (NF2), and schwannomatosis as complex genetic abnormalities that may affect many different organ systems in the body. When alterations in the gene NF1, located in the 17th chromosome occur, it causes NF1 type disorder. NF1 gene controls the synthesis of a specific protein called neurofibromin that functions as a tumor suppressor. The predisposition to form tumors, often on the nerves, spine, brain, and skin, is a common characteristic of these disorders. But the types and severity of symptoms vary widely among individuals. Here, we present a case of NF-1 with a severe infective tumor lesion on the left hand. A 56-year-old male was admitted to the dermatology department with a chief complaint of a mass lesion on the hand that was painful, severely itchily, and progressively increased in size. Multiple neurofibromas were found on his body that are soft, fleshy tumors arising from a peripheral nerve sheath near the surface of the skin, or on the skin, and he had already been diagnosed in his childhood as neurofibromatosis.